Comparative study of the smear microscopy, with conventional culture in clinically suspected cases of pulmonary and extra pulmonary tuberculosis - Singh, Paramjit; Chauhan, Sapna; Lakshmikantha, Mapary; Tiwari, Swati; Sharma, Sachin (International Journal of Research in Medical Sciences, 2017)
Background: Tuberculosis is a significant cause of morbidity and mortality in the Indian subcontinent. A major challenge to clinical microbiology is the detection of Mycobacterium tuberculosis as accurately as possible. Objective: Tthe most important tool in the diagnosis of tuberculosis is direct microscopic examination of appropriately stained specimens for acid- fast bacilli and the gold standard for diagnosing tuberculosis is MTB convention culture on L-J media So, the present study was undertaken to compare smear microscopy by Z – N staining with conventional culture on L-J media, in cases of clinically suspected Pulmonary Tuberculosis and Extra Pulmonary Tuberculosis. Methods: 279 samples were processed within 24 hours of receipt. Samples from non-sterile sites were subjected to decontamination by the modified Petroff’s method. Sterile samples were directly processed as per conventional methods. Smear microscopy was done by Z- N staining and culture was done on L- J media. A control organism in the form of M. tuberculosis H37Rv was also tested with each batch of clinical isolates. Result: Results of smear microscopy and conventional culture of pulmonary and extra pulmonary specimens were compared. 22 and 14 more cases were detected by culture as compared to smear in case of pulmonary and extra pulmonary specimens respectively. Conclusion: From this study we can state that direct microscopic examination of appropriately stained Pulmonary and Extra Pulmonary specimens for acid fast Bacilli is an important tool in the diagnosis of tuberculosis. The Technique is simple, inexpensive and fast .However many Paucibacillary cases may be missed on smear microscopy. Thus specimens from all suspected cases of Pulmonary and Extrapulmonary Tuberculosis should be subjected to conventional culture on LJ media. This is the Gold Standard for Diagnosing Tuberculosis.